Pesticide-free agriculture as a new paradigm for research - Jacquet, Florence; Jeuffroy, Marie-Hélène; Jouan, Julia; Le Cadre, Edith; Litrico, Isabelle; Malausa, Thibaut; Reboud, Xavier; Huyghe, Christian (Agronomy for sustainable development, 2022)
Reducing pesticide use has become a goal shared by several European countries and a major issue in public policies due to the negative impacts of pesticides on the environment and on human health. However, since most of the agri-food sector relies on pesticides in these countries, substantially reducing pesticide use is a complex issue. To overcome this situation, we argue that agricultural research has a major role to play and must adopt a pesticide-free paradigm to expect a deep impact on pesticide use. In this article, we explain why this new paradigm is needed and outline research fronts that it will help address. These research fronts are related to five strategies: (1) redesigning cropping systems to enhance prophylaxis, (2) diversifying biocontrol strategies and associated business models, (3) broadening the scope of plant breeding to include functional biodiversity and evolutionary ecology concepts, (4) setting new goals for agricultural machinery and digital technologies, and (5) supporting development of public policies and private initiatives for the transition toward pesticide-free agri-food systems. The corresponding research activities must be managed conjointly to develop systemic and coupled innovations, which are essential for reducing pesticide use significantly. We therefore provide examples of cross-cutting objectives that combine these fronts while also highlighting the need for interdisciplinary research projects. By doing so, we provide an overall orientation for research to achieve sustainable agriculture.